Abordagem terapêutica do pneumotórax em cães: revisão sistemática - Bomfim, Larissa da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Pneumothorax can be defined as an accumulation of air or gas in the pleural space. The objective of this study was to evaluate the main forms of therapeutic approach in the pneumothorax in the canine species and to analyze whether or not they have proven reliability in the literature. A systematic literature review was conducted using nine articles retrieved from the PubMed and Google academic databases. The main search strategy used was the following: pneumothorax treatment AND (dogs). The work was classified according to the scales of Jadad et al. (1996) and Cook et al. (1995). It was concluded that traumatic causes are solved with medical treatment, while spontaneous ones need a surgical therapeutic approach. The treatments analyzed were: thoracentesis, video-assisted surgery in association with aortic or total lobectomy, autologous blood pleurodesis, thoracotomy associated with pleurodesis, thoracotomy associated with thoracotomy and lobectomy, and transdiaphragmatic xiphoid thoracoscopy associated with thoracic drainage. That said, in general, the authors considered the different behaviors as therapeutically effective. However, most of these articles presented a small sample group, thus not having a satisfactory quality and reliability, which demonstrates the need for new studies.

O pneumotórax pode ser definido como um acúmulo de ar ou gás no espaço pleural. O objetivo desse trabalho foi avaliar as principais formas de abordagem terapêutica no pneumotórax na espécie canina e analisar se as mesmas possuem ou não confiabilidade comprovada pela literatura. Foi realizada uma revisão sistemática de literatura utilizando-se nove artigos retirados dos bancos de dados PubMed e Google acadêmico. A principal estratégia de busca utilizada na pesquisa foi a seguinte: "pneumothorax treatment" AND (dogs). Os trabalhos foram classificados de acordo com as escalas de Jadad et al. (1996) e de Cook et al. (1995). Concluiu-se que causas traumáticas resolvem-se com o tratamento médico, já as espontâneas, necessitam de uma abordagem terapêutica cirúrgica. Os tratamentos analisados foram: toracocentese, cirurgia vídeo-assistida em associação com a lobectomia pacial ou total, pleurodese com sangue autólogo, toracotomia associada à pleurodese, toracocentese associada à toracotomia e lobectomia e toracoscopia xifoide transdiafragmática associada à colocação de dreno torácico. Isso posto, de uma maneira geral, os autores consideraram as diferentes condutas como terapeuticamente efetivas. No entanto, a maioria desses artigos apresentou grupo amostral pequeno, não possuindo, assim, uma qualidade e confiabilidade satisfatórias, o que demonstra a necessidade de realização de novos estudos.
Keywords: Pneumoperitônio; Pneumoperitônio - Tratamento; Cães; Therapeutic approach